2019
DOI: 10.1186/s12917-019-2101-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal parasites in free-range yaks (Bos grunniens) in Gansu Province, Northwest China

Abstract: BackgroundLittle information about the prevalence of gastrointestinal parasites in yaks (Bos grunniens) in northwest China is available. Therefore, the objective of the study was to quantify faecal egg counts of gastrointestinal parasites (helminths and coccidia) in free-range yaks from Gannan Tibetan Autonomous Prefecture, Gansu Province, Northwest China.ResultsParasites were detected in 290 of 733 (39.56%) faecal samples. The results showed that Strongylidae, Trichuris spp. and Eimeria spp. were detected all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There are several studies proving that BVDV is prevalent worldwide. In Tibet and Qinghai of western China, seropositivity rates were above 53% in yaks, and the BVDV positivity rate was 35–41% in Gansu Province, 77.8% in Eastern China, and 100% in Shanxi Province ( Gao et al, 2013 ; Hou et al, 2019 ; Qin et al, 2019 ; Ma et al, 2016 ; Deng et al, 2020 ). Ricci et al (2019) found that BVDV-1 was detected in unvaccinated cattle in Italy (28%), and the positive rates was higher than 67% in Uruguay, Turkey and other countries ( Maya et al, 2020 ; Timurkan & Aydın, 2019 ; Aragaw et al, 2018 ; Nugroho et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies proving that BVDV is prevalent worldwide. In Tibet and Qinghai of western China, seropositivity rates were above 53% in yaks, and the BVDV positivity rate was 35–41% in Gansu Province, 77.8% in Eastern China, and 100% in Shanxi Province ( Gao et al, 2013 ; Hou et al, 2019 ; Qin et al, 2019 ; Ma et al, 2016 ; Deng et al, 2020 ). Ricci et al (2019) found that BVDV-1 was detected in unvaccinated cattle in Italy (28%), and the positive rates was higher than 67% in Uruguay, Turkey and other countries ( Maya et al, 2020 ; Timurkan & Aydın, 2019 ; Aragaw et al, 2018 ; Nugroho et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the previous traditional studies, most researchers showed that yaks were infected with F. hepatica. During 1996 to 2020, the prevalence of F. hepatica was reported in major yak-producing areas in China such as the Tibetan Autonomous Region (18.33%-100%) [16,22,23], some counties in Qinghai province (16.7%-97%) [24][25][26][27][28][29], the northwest of Sichuan province (23%) [30], and Gansu province (6.55%-42.5%) [15,31]. In addition, the prevalence of Fasciola was 10% in India and 16.67% in Nepal [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Data reflecting the ruminant health status and behavioral activities of yaks and goats from the Plateau with similar living conditions were collected [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The blood indexes, parasitic infection rates, and grazing behaviors of wild yaks, captive yaks, wild goats, captive blue sheep, and captive European mouflons were analyzed.…”
Section: Methodsmentioning
confidence: 99%